How frequently should a patient taking amiodarone be screened for thyroid dysfunction? - Pazin-Filho,A. (2009)
Amiodarone-induced thyroid dysfunction (AITD) is a common complication of amiodarone therapy and its prevalence varies according to iodine intake, subclinical thyroid disorders and the definition of AITD. There is no consensus about the frequency of screening for this condition. We evaluated 121 patients on chronic regular intake of amiodarone (mean intake = 248.5 ± 89 mg; duration of treatment = 5.3 ± 3.9 years, range = 0.57-17 years) and with stable baseline cardiac condition. Those with no AITD were followed up for a median period of 3.2 years (range: 0.6-6.7) and the incidence rate of AITD, defined by clinical and laboratorial findings as proposed by international guidelines, was obtained (62.8 per 1000 patients/year). We applied the Cox proportional hazard model to adjust for potential confounding factors and used sensitivity analysis to identify the best screening time for follow-up. We detected thyroid dysfunction in 59 (48.7%) of the 121 patients, amiodarone-induced hypothyroidism in 50 (41.3%) and hyperthyroidism in 9 (7.5%). Compared with patients without AITD, there was no difference regarding dosage or duration of therapy, heart rhythm disorder or baseline cardiac condition. During the follow-up of the 62 patients without AITD at baseline evaluation, 11 developed AITD (interquartile range, IR: 62.8 (95%CI: 31.3-112.3) cases per 1000 patients/year), 9 of them with hypothyroidism - IR: 11.4 (95%CI: 1.38-41.2), and 2 hyperthyroidism - IR: 51.3 (95%CI: 23.4-97.5). Age, gender, dose, and duration of treatment were not significant after adjustment. During the first 6 months of follow-up the incidence rate for AITD was 39.3 (9.2-61.9) cases per 1000 patients/year. These data show that AITD is quite common, and support the need for screening at 6-month intervals, unless clinical follow-up dictates otherwise or further information regarding the prognosis of untreated subclinical AITD is available.